2014
DOI: 10.1007/s13205-014-0245-6
|View full text |Cite|
|
Sign up to set email alerts
|

Production of chitin and bioactive materials from Black tiger shrimp (Penaeus monodon) shell waste by the treatment of bacterial protease cocktail

Abstract: The main objective of this study was to obtain chitin in pure form from a new crustacean waste material for industrial applications. Black tiger shrimp shell wastes are a rich source of protein and valuable bioactive carbohydrate polymers such as chitin. After removal of carotenoid, Black tiger shrimp shell wastes (BTSHWs) were treated with chemicals and protease enzyme to extract chitin. Box–Behnken response surface methodology was applied to optimize the deproteinization process to obtain chitin. At optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Recently, Zhuang et al investigated the effect of deacetylation degree on mechanical and barrier properties of chitosan films with three different DD values, 81.0%, 88.1% and 95.2%, wherein CH films with higher DD values (88.1% and 95.2%) were found to have better water barrier property and tensile strength compared to films obtained with a chitosan value of 81.0% DD [37]. It has been reported that the antimicrobial efficiency also improves with the increase in the degree of deacetylation of chitosan that is generally attributed to the increase in the number of positive charges from the amine groups [39].…”
Section: Chitin Chitosanmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, Zhuang et al investigated the effect of deacetylation degree on mechanical and barrier properties of chitosan films with three different DD values, 81.0%, 88.1% and 95.2%, wherein CH films with higher DD values (88.1% and 95.2%) were found to have better water barrier property and tensile strength compared to films obtained with a chitosan value of 81.0% DD [37]. It has been reported that the antimicrobial efficiency also improves with the increase in the degree of deacetylation of chitosan that is generally attributed to the increase in the number of positive charges from the amine groups [39].…”
Section: Chitin Chitosanmentioning
confidence: 94%
“…DD indicates the amount of amino groups in chitosan polymer, which will affect the properties of chitosan, such as charge, density, solubility, crystallinity, degradation behaviour, mechanical, barrier, and thermal properties [37][38][39]. An increased percentage of amino groups in chitosan polymer makes it soluble in weak acids, a characteristic difference from chitin.…”
Section: Chitin Chitosanmentioning
confidence: 99%
“…For all these reasons, other technologies for the deproteinization step of chitin production, like microbial treatment (by lactic acid and miscellaneous fermentation) and enzymatic processes using crude extracts and/or isolated enzymes, have been proposed (Healy et al, 1994;Gildberg and Stenberg, 2001; Rao and Stevens, 2005;Duan et al, 2012;Hajji et al, 2014;Paul et al, 2015). The use of enzymes for deproteinization of crustacean shells, avoiding the necessity of strong alkaline treatments during this stage, has been considered since they are specific, fast in action and, most of times, reduce the use of energy, chemicals and/or water, when compared with conventional processes (Jegannathan and Nielsen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the existence of an acetyl group or rather, a lack thereof, at the reducing and non-reducing sugar ends, as well as neighbouring variants, nuclear magnetic resonance (NMR) is employed. Studies have made use of both 1 H NMR [92,133] and 13 C NMR [7,175] to obtain sequence information of short COS of up to DP 5. Since the acquired information is merely limited to the average frequency of diads and triads, no definitive structure for COS mixtures can be obtained.…”
Section: Quantitative and Qualitative Separation Of Cos Mixturesmentioning
confidence: 99%